2019
DOI: 10.1073/pnas.1901307116
|View full text |Cite
|
Sign up to set email alerts
|

Responses of tundra soil microbial communities to half a decade of experimental warming at two critical depths

Abstract: Northern-latitude tundra soils harbor substantial carbon (C) stocks that are highly susceptible to microbial degradation with rising global temperatures. Understanding the magnitude and direction (e.g., C release or sequestration) of the microbial responses to warming is necessary to accurately model climate change. In this study, Alaskan tundra soils were subjected to experimental in situ warming by ∼1.1 °C above ambient temperature, and the microbial communities were evaluated using metagenomics after 4.5 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
95
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 95 publications
(112 citation statements)
references
References 79 publications
(76 reference statements)
3
95
3
Order By: Relevance
“…Shifts of the optimum temperature of net ecosystem exchange are mostly due to temperature acclimation of GPP. The optimum temperature for ecosystemlevel GPP, however, is consistently lower than the physiological optimal temperature of leaf-level photosynthesis (Huang et al, 2019).…”
Section: Chang Ing Propertie S Of E Volving Sys Temsmentioning
confidence: 80%
See 1 more Smart Citation
“…Shifts of the optimum temperature of net ecosystem exchange are mostly due to temperature acclimation of GPP. The optimum temperature for ecosystemlevel GPP, however, is consistently lower than the physiological optimal temperature of leaf-level photosynthesis (Huang et al, 2019).…”
Section: Chang Ing Propertie S Of E Volving Sys Temsmentioning
confidence: 80%
“…For example, the optimal temperature at which photosynthesis is maximized is a property of photosynthetic systems. This property has been documented to ubiquitously vary at leaf, plant, and ecosystem scales as temperature changes through photosynthetic acclimation and adaptation (Berry & Bjorkman, 1980;Huang et al, 2019;Mooney, Björkman, & Collatz, 1978;Niu et al, 2012). Data synthesis from 169 globally distributed sites of eddy covariance shows that the optimum temperature of net ecosystem exchange is positively correlated with annual mean temperature over years and across sites (Niu et al, 2012).…”
Section: Chang Ing Propertie S Of E Volving Sys Temsmentioning
confidence: 99%
“…A meta-analysis of 75 manipulative experiments found that the response of soil communities to warming experiments were best explained by local climate and ecosystem type [67]. Although peat community structure hasn't responded to ex-situ warming in this experiment or in-situ warming in the early SPRUCE experiment, continued long-term warming of SPRUCE plots may lead to altered community structure much like the delayed response seen in other long term soil warming experiments in upland and tundra soils [15,68,69]. However, while peatland microorganisms could be considered 'slow growers' and thus need more time for observable shifts in community structure, we did witness significant shifts in community indicators with other experimental factors, suggesting a lag between physiological response and community structure that is specific to increased temperature.…”
Section: Role Of Microbial Communitymentioning
confidence: 85%
“…The classes Alpha-, Beta-and Gammaproteobacteria, and Acidobacteria were, in proportion, the dominant bacterial taxa in the avocado soil and rhizosphere samples. These bacterial classes are the most frequently found in high C:N soil (Hermans et al, 2017) and are easily found in soil with the presence of organic matter in decomposition (Johnston et al, 2019). This is the case of the avocado soils of southern Spain, where attempts have been made to increase the low levels of organic matter by leaving leaf litter and chopped pruning waste on the top layer of soil every year (Bonilla et al, 2012) or where organic matter are currently used as amendments (Vida et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…This fungus can attack the plant roots, multiply and expand its hyphae inside the roots, necrotizing the plant living tissues, and finally survive in the decomposing organic matter overwinter (Pliego et al, 2009(Pliego et al, , 2012. It has been previously described that the presence of a dominant soil fungus can influence the soil and rhizosphere microbial communities (de Boer et al, 2015;Johnston et al, 2019), and in our study, the presence of R. necatrix impacted the microbial communities, mainly because they are dependent on the ecological strategy of the dominant fungus (Johnston et al, 2019). The prokaryotic populations of soil and rhizosphere samples showed a slight response to this new biological factor; mainly, the relative abundance of families containing chitinolytic bacteria increased (Chitinophagaceae and Cytophagaceae).…”
Section: Discussionmentioning
confidence: 99%